The Basic Aspects of the Hyman Minsky’s Financial Instability Hypothesis - Rozmainsky, I. (Економічний вісник Донбасу, 2017)
This paper considers the basic aspects of the financial instability hypothesis developed by Hyman Minsky. This conception has become very pertinent due to the events concerned with the Great Recession. The author shows both links between Keynes’s theory and Minsky approach and Post Keynesian “spirit” of the described hypothesis. The special role of uncertainty and money has been emphasized. The paper shows that the hypothesis provides an understanding of how the contemporary market capitalist economy endogenously becomes “financially fragile” and thus prone to crises. The author demonstrates that the Great Recession can be treated as a consequence of the processes described by the financial instability hypothesis.